Valutazione linguistica in italiano e nella LIS e strategie di intervento (Fondazione Università Ca' Foscari, 2024)
This volume gathers some original studies conducted by graduates of the Department of Linguistics and Comparative Cultural Studies at Ca’ Foscari University of Venice, who have contributed to the research in linguistics through the description of the linguistic competence of individuals whose access to language is compromised, and whose ability to verbally express themselves is limited or completely hindered. Thanks to their contributions, targeted linguistic strategies have also been developed to promote the enhancement of language and communication skills in some of these individuals. The first article provides some observations on the methods and tools available for assessing and improving linguistic competence in contexts of deafness and communication disabilities. Three articles focus on describing the linguistic competence of different groups of deaf or hard-of-hearing adults, assessing some linguistic properties (clitic pronouns and interrogative sentences) in Italian, and narrative abilities in Italian and Italian sign language. One contribution focuses on the case of a deaf girl of foreign origin with extremely poor linguistic competence in Italian. Teaching activities have been proposed using various multimedia and multimodal tools to enhance her language skills in Italian and her communicative abilities. The final contribution, following a similar approach, describes the communication methods based on the use of signs proposed to a girl with a phonological and articulatory disorder to allow her to interact with the people around her.